2018
DOI: 10.1186/s40360-018-0268-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid damage is the best marker of oxidative injury during the cardiac remodeling process induced by tobacco smoke

Abstract: BackgroundOxidative stress is one potential mechanism that explain the direct effects of smoking on cardiac remodeling process. However, no study has compared different myocardial products of macromolecule oxidation after tobacco smoke exposure. Thus, the aim of this study was to investigate the lipid hydroperoxide (LH) levels, protein carbonyl concentrations and DNA damage in cardiac tissue of rats exposed to tobacco smoke.MethodsMale Wistar rats were divided into two groups: group C (control, n = 14) compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…Regarding the association between smoking behavior and vitamin E levels, a strong association was observed between current smoking and α-CEHC. This is in accordance with multiple other studies, all linking smoking to various measurements of increased oxidant activity [ 25 , 39 , 40 , 41 ]. Although our data showed that both the oxidative as well as enzymatic conversion of α-TOH were lower in current smokers, our data does suggest that there is relatively more oxidative conversion as enzymatic conversion, which is reflected by higher TLHQ relative to CEHC levels in current smokers.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the association between smoking behavior and vitamin E levels, a strong association was observed between current smoking and α-CEHC. This is in accordance with multiple other studies, all linking smoking to various measurements of increased oxidant activity [ 25 , 39 , 40 , 41 ]. Although our data showed that both the oxidative as well as enzymatic conversion of α-TOH were lower in current smokers, our data does suggest that there is relatively more oxidative conversion as enzymatic conversion, which is reflected by higher TLHQ relative to CEHC levels in current smokers.…”
Section: Discussionsupporting
confidence: 93%
“…Twenty‐four male Wistar rats, weighing between 200 and 250 g, were divided into two groups: the control group (not exposed to cigarette smoke) (C; n = 12) and the cigarette smoke‐exposed group (exposed to cigarette smoke over the 2 months) (CS; n = 12). The exposure to cigarette smoke for 2 months was performed according to the previously standardized method from our laboratory 1,5 …”
Section: Methodsmentioning
confidence: 99%
“…This study further explores the impact of cinnamon-flavored e-liquids on collagen type I protein expression to determine how e-cigarette could affect bone health. Conventional tobacco cigarette is also known to induce oxidative stress both in in vitro and in vivo experiments, increasing production of reactive oxygen species (ROS) in ovarian cells [31], elevating intracellular oxidative stress in corneal epithelial cells [32], causing oxidative lipid damage in rats [33], and inducing cardiovascular mitochondrial oxidative stress in mouse models [34,35].…”
Section: Introductionmentioning
confidence: 99%